Uncovering Botrytis cinerea-induced physiological changes in melon plants using multi-sensor imaging approaches - Matilde Barón; María Trinidad Moreno-Martín; Mónica Pineda (Plant Stress)
Botrytis cinerea, a necrotrophic fungus, poses a challenge to melon cultivation, causing severe damage leading to reduced crop yields. Understanding the infection process of B. cinerea is crucial for developing effective control strategies against it in agricultural and horticultural environments. Traditional methods for studying metabolic changes in host plants are time-consuming and, if imaging techniques are used, usually involve a single sensor. This research takes advantage of multiple imaging tools - RGB, thermal, chlorophyll fluorescence, blue-green fluorescence and hyperspectral reflectance devices - to capture a complete picture of physiological changes in melon leaves infected by this fungus. By comparing infected areas with adjacent healthy tissues, key metabolic changes are identified, such as decreased photosynthetic activity and increased oxidative stress, which occur even before visible symptoms appear. The images provide a detailed spatio-temporal map of infection progression and host response, revealing critical aspects of this plant-pathogen interaction. These results highlight the value of integrating multiple imaging technologies for early detection and management of fungal infections in crops. The results also suggest potential applications for precision agriculture, offering a more efficient way to monitor plant health and implement targeted interventions.